New Sweet Potato Genotypes: Analysis of Agronomic Potential - Dango, F.J.U.; Oliveira, D.J.L.S.F.; Otoboni, M.E.F.; Pavan, B.E.; Andrade, M.I.; Vargas, P.F. (2025)
The quantification of genotype x environment interaction is essential for recommending high-yielding genotypes for both favorable and unfavorable environments, thereby increasing production. This study aimed to evaluate the agronomic performance of sweet potato genotypes in the central–east and central–south regions of São Paulo. The experiments were conducted using a randomized block design with 9 plants per plot and 3 replications, consisting of 18 sweet potato genotypes and 3 commercial cultivars, totaling 21 treatments. The characteristics, such as commercial productivity, dry matter, chroma, hue, insect resistance, eyes, and lenticels showed genotype x environment interaction for 77.78% of the variables. The maximum productivity of the genotypes ranged from 31.81 t/ha−1 to 63.60 t/ha−1. Heritability was observed in 88.89% of the analyzed traits, with values ranging from 75.36% to 93.47%, indicating a significant genetic influence on the evaluated characteristics. Location 4 (first cycle in Botucatu, 20 December 2021) was superior and considered the most suitable for sweet potato cultivation. The genotypes CERAT60-05, CERAT56-23, CERAT60-26, and CERAT35-11 performed best, showing promise as new cultivars.